Charlemagne - Becher, Matthias (Yale University Press, 2003)
"Charlemagne - ruler of the vast Frankish kingdom from 768 to his death in 814 and emperor from the year 800 - is considered the father of Europe. He founded the first empire in western Europe after the fall of Rome, and his court at Aix-la-Chapelle was a center of classical learning and a focus of the Carolingian Renaissance. This book is an introduction to Charlemagne's life and legend."--Jacket